2009
DOI: 10.1007/s00011-008-8215-2
|View full text |Cite
|
Sign up to set email alerts
|

ApoE phenotype is associated with inflammatory markers in middle-aged subjects

Abstract: ApoE phenotype is an independent determinant of plasma resistin and hsCRP levels. The extent of atherosclerosis and renal function seem to modify the effects of apoE phenotype on inflammatory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Our results that E3E4 and E4E4 genotype are associated with lower CRP levels are in agreement with previous studies ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). In a few studies, there was no association between APOE E4 allele and low CRP levels ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results that E3E4 and E4E4 genotype are associated with lower CRP levels are in agreement with previous studies ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). In a few studies, there was no association between APOE E4 allele and low CRP levels ( 30 , 31 ).…”
Section: Discussionsupporting
confidence: 94%
“…Since Manttari and colleagues first described the association of APOE E4 allele with low CRP levels in 2001, many studies have investigated relationships between APOE genotype and CRP levels. Most studies have reported that E4 allele is associated with low levels of CRP ( 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ). However, there is little research on the relationship between other markers of inflammation and APOE genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to APOEε2 and APOEε3 carriers, APOEε4 carriers generate less ApoE protein in periphery and brain ( Larson et al, 2000 ). Given the reduced amounts of ApoE protein in APOEε4 carriers, this population could be predisposed to a heightened inflammatory response when encountering a sterile inducer or infection ( Ukkola et al, 2009 ; Gale et al, 2014 ; Tai et al, 2015 ).…”
Section: Apoeε4 Inflammation and Alzheimer’s Diseasementioning
confidence: 99%
“…Surprisingly, however, this is not the case, at least with CRP. Studies have consistently shown that CRP levels are lower in APOEε4 carriers ( Ukkola et al, 2009 ; Lima et al, 2014 ; Metti et al, 2014 ; Yun et al, 2015 ). Marz et al (2004) proposed that the metabolism of CRP might be associated with the mevalonate/cholesterol synthetic pathway, which might be downregulated in APOEε4 carriers.…”
Section: Apoeε4 Inflammation and Alzheimer’s Diseasementioning
confidence: 99%
“…Eighteen studies 12,13,[15][16][17][18][19][20][21][22][26][27][28][29][30][31][32]34 were included into the study of e4 versus e3 (including 29 comparisons). Seventeen studies 12,13,[15][16][17][18][19][20][21][22][26][27][28][29][30][31][32] were included into the study of e2 versus e4 (including 27 comparisons).…”
Section: Study Characteristics For the Relationship Between Apoe Genementioning
confidence: 99%